Anatomical Studies on the Hair Follicles of Skin of Bakerwali Goat - Razvi, Raheeqa; Suri, Shalini; Sarma, Kamal (Indian Journal of Veterinary Anatomy, 2016)
Anatomical studies on hair follicles of skin of Bakerwali goat was conducted in neonatal, young and adult age groups. Tissue samples were collected form neck, thorax and loin regions of Bakerwali goat. Hair follicles seemed to be the extensions from the papillary layer of the skin dermis which opened externally through skin epidermis. Hair follicles were arranged in single or double tire arrangement. The two types of hair follicles were seen i.e. the primary and secondary hair follicles. The primary hair follicles were associated with sweat glands, sebaceous glands and arrector pili muscles, while the secondary hair follicles were commonly associated with sebaceous glands. The diameter of secondary hair follicles was lesser than primary hair follicles. The depth of primary hair follicles was more in adult age group as compared young and neonatal age group. The density of hair follicles was found to be maximum in dorsal regions than lateral regions. These hair follicles were oriented at an oblique angle to the skin surface in all regions and age groups under study. Cross section of hair follicle had an outer root sheet, an inner root sheath, cortex and medulla. In the present study, the hair follicles showed strongly positive reaction in outer layer, moderate alcian blue reaction in middle layer and moderate PAS reaction in inner layer with Combined Alcian blue stain indicating the presence of neutral and acidicmucopolysaccharides respectively.